Impact of insufficient admission vitamin D serum concentrations on sepsis incidence and clinical outcomes in patients with thermal injury. Issue 1 (February 2020) - Zavala, S.; Larson, J.; O'Mahony, M.; Rech, M.A.
Highlights: Adult burn patients with adequate vitamin D levels on admission were associated with decreased incidence of sepsis. Burn patients with insufficient vitamin D had longer hospital length of stay and longer intensive care unit length of stay. Burn patients with insufficient vitamin D had fewer ventilator free days. No difference in mortality was found between burn patients with insufficient vitamin D and those with adequate vitamin D. Abstract: Introduction: In burn patients, vitamin D has been studied primarily in the pediatric population and focused mainly on the correlation with bone marker measurements and incidence of fractures. There is an association between vitamin D deficiency and the development of sepsis in non-burn critically-ill patients. However, there is limited data on vitamin D concentrations and clinical outcomes in burn patients, such as sepsis. The objective of this study is to evaluate the impact of vitamin D concentrations on the incidence of sepsis in adult burn patients. Methods: This was a retrospective cohort of patients 18 years of age and older admitted between February 1, 2016 and February 28, 2018 to an American Burn Association (ABA) verified burn center with diagnosis of burn injury. The primary endpoint was incidence of sepsis using the ABA 2007 Sepsis Consensus Criteria between patients with adequate vitamin D concentrations (25[OH]D > 20 ng/mL) and insufficient vitamin D (25[OH]D < 20 ng/mL) concentrations measured on admission. Descriptive statistics were used for baseline demographics. Univariate analysis was conducted using Chi-square, Fisher's exact test or Mann–Whitney U test, as appropriate. Results: A total of 115 patients were screened and 107 patients were included in this study. Sixty three patients (58.9%) had insufficient vitamin D concentrations. Patient demographics were overall similar between groups. The median total body surface area burned was 14.6% in the insufficient vitamin D group, and 12.1% in the adequate vitamin D group (p = 0.2). There was a trend towards greater incidence of sepsis in the insufficient vitamin D group in the univariate analysis (15.9% vs. 4.5%, p = 0.07). The multivariable logistic regression analysis found that adequate vitamin D concentrations was associated with a reduction in the incidence of sepsis (OR 0.10, 95% CI 0.01–0.88). The insufficient vitamin D group had a longer median hospital LOS (19 [IQR 11–37] vs 11.5 [IQR 7–20] days, p < 0.05), longer intensive care unit LOS (17 [IQR 10–37] vs 5 [IQR 2–19.5] days, p < 0.05) and fewer ventilator free days (26 [IQR 18–28] vs 28 [IQR 27–28] days, p < 0.05). There was no difference in mortality between groups (p = 0.69). Conclusions: Patients with adequate vitamin D concentrations on admission had a reduction in the incidence of sepsis as compared to patients with insufficient vitamin D concentrations. Insufficient vitamin D concentrations may contribute to other worsened clinical outcomes in burn patients. Our findings set the stage for future, multicenter studies to determine the role of vitamin D supplementation in burn patients.